POTENSI TUMBUHAN OBAT DI DESA BEMBAN KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG KECAMATAN KUBU KABUPATEN KUBU RAYA - Rianti, Yuli; Purwati, Purwati; Wahdina, Wahdina (JURNAL HUTAN LESTARI, 2019)
The potential of forest products is not only in the form of timber, but also other valuable benefits that can contribute to human life such as medicinal plants for health. Medicinal plants are plants that have functions and nourishments as medicine and used for therapy or prevention of various diseases. The term â€œmedicinalâ€ itself means â€œ to contain certain active substances that can treat certain diseases and contain certain active substances, contain a resultant effect or synergy of various substances which have the healing effects. This research aims to assess the potential and utilization of medicinal plants and herbs found in Bemban Village in the Protected Forest Area of Gunung Ambawang of Kubu Subdistrict, Kubu Raya Regency. The research was carried out in Bemban Village in the Protected Forest Area of Gunung Ambawang of Kubu Subdistrict, Kubu Raya Regency for more or less 4 weeks effective in the field. The vegetation analysis method in the field of the research was carried out with plot line method placed by purposive sampling. The research sites had 3 observation lines with a plot length of 100-300 m, the number of observation plots was 12 plots and each plot area was 0,04 ha with distance between the plots in one line was 50 m. So, the total area of observation was 0,04 ha. The results showed that there were 87 medicinal plant species of 59 families. A total of 58 medicinal plant species of 34 families were taken directly by the community around the yard, and 29 species of medicinal plants of 25 families found from the analysis of the vegetation in the field. Â Keywords: Bemban Village, Gunung Ambawang, Medicinal Plants